Storm-associated variations of [OI] 630.0 nm emissions from low latitudes - Mukherjee, G.K. (My University, 1999)
The ground-based magnetic signature of particle precipitation from the ring current to low latitude regions during the recovery phase of a geomagnetic storm on 23 December, 1995, has been inferred by studying photometric 630.0 nm nightglow at a low latitude station, Kolhapur (7.5N, 144.7E; Geomagnetic, dip latitude 10.6N) and magnetograms (H, D and Z) of nearby low latitude stations. The maximum optical emission occurred simultaneously with the maximum positive (north ward) excursions in the H trace of low latitude magnetograms associated with negative H excursions at high latitude observatories. Generally, an increase in Z component occurred at all low latitude stations. A large intensity increase of about seven times in 630.0 nm emission was observed at around 2:15 hrs L.S.T on 23 December, 1995. The 630.0 nm enhancement maximized at the time of high Dst or Kp index during the night. In addition, the ionosonde experiment conducted at Ahmedabad (13.8N, 144E; Geomagnetic) showed the ehhancement of peak electron densities in the F-region and sudden lowering of the F layer in the ionosphere. A possible explanation of the effect is given in terns of emergence of energetic neutral atoms (Hydrogen or Oxygen) from high energy protons in a typical charge exchange process in the ring current depositing energy into composition of the thermosphere-ionosphere during magnetic storms that would enhance the 630.0 nm emissions.
Keywords: Ionosphere; Airglow; Precipitation; Low latitudes